THE SCOR METHOD FOR MEASURING PERFORMANCE - THE WAY TO MONITOR THE PERFORMANCE OF ENTERPRISE LOGISTICS - Majercak, Jozef; Majercak, Peter (Doprava a spoje, 2012)
The paper deals with a very actual topic about a methods for measuring logistics performance. The SCOR is a model that combines business processes, metrics, best practices and technological solutions into a single structure that supports communication between the elements of the supply chain. The authors describe precisely the methods for measuring performance such as benchmarking and SCOR model.